A Study of the Effect of Using Orange Peel Powder on the Most Important Characteristics of High-Fiber Bran Flat and Double-Layer Bread (Journal of Hama University, 2024)
Bran bread, prepared from a mixture of wheat flour and bran, is one of the most important functional foods and therefore there is a need to enhance its health benefits and nutritional value. The orange peels, that are resulting from the orange juice factories, are also considered a promising by-product in the field of food industry. So, the effect of using different ratios of orange peel powder (2.5, 5, 7.5, and 10)% on some physical and rheological properties of flour, as well as the sensory and chemical properties of bran bread was determined. The results of the flour mixtures study showed a significant decrease in wet gluten, falling number, and sedimentation number (P
Keywords: orange peels, high-fiber flat bran bread, chemical composition, rheological properties, sensory evaluation